Pengembangan LKS Matematika Berbasis Problem Based Learning (PBL) untuk Siswa Kelas V Sekolah Dasar - Joni Ariso; Agus Susanta; Abdul Muktadir (Universitas Bengkulu, 2023)
The research aims to develop a Problem Based Learning (PBL) based Mathematics worksheet for Grade V elementary school students that is feasible and practical. This research is research development. The method used is R & D by adapting 6 steps of development from Sugiyono namely (1) potential problems, (2) information gathering, (3) product design, (4) design validation, (5) product revisions, (6) product trials. The subject in this study were fifth grade students at SDN 58 Bengkulu Selatan. The instruments used were questionnaires and interview guidelines for needs analysis, expert validation. The results showed that the worksheet developed were feasible and practically used. Worksheets developed are very practically for use by students and teachers in learning. This is indicated by the results of the analysis of student responses that are in the criteria of